Holistic Dynamics of Urban Pond Infrastructure for Flood Risk Mitigation – A Case Study on Jaffna Municipal Council Area - Thawsika, S.; Rajapakse, R.L.H. (University of Jaffna, 2022)
The frequency of flood occurrence in the Jaffna Peninsula mainly depends on rainfall intensity, conditions of natural drainage, associated terrain, and hydraulic structures. Jaffna Municipal area has also been facing recurrent severe flood events in the past years. Since it is situated in the dry zone, the seasonal rainfall occurs in the second inter monsoon and North-East monsoon periods with daily rainfall often exceeding monthly average rainfall under extreme conditions and there is no proper management of drainage network or associated pond cascades. However, in the past, these cascade pond systems were used to retain the upstream rainwater and enrich groundwater storage through recharging before it reaches the outlet. In the present study, a pond cascade model was developed by using the HEC ResSim computer simulation application to compare the efficiency of flood mitigation of cascade systems and individual ponds. The HEC-HMS computer application was used to find runoff from the catchment. The flood inundation area was identified by the HEC-RAS 5.0.7 modeling. According to the results obtained from the model calibration based on the 2017-year rainfall event and 10-year return period flood event, the flood inundation area of the individual pond approach was 0.366. When the cascade pond behavior was introduced, it was reduced to 0.2352 km2. The obtained results obviously say that the flood inundation area was reduced by the pond cascade system because a considerable amount of flood was retained in upstream ponds. The inundation area was decreased by 0.1308 km2. It is possible to reduce the flood inundation area further based on the results by increasing the pond capacities. In conclusion, the flood inundation can effectively be reduced by ensuring the holistic behavior of the pond cascade system meanwhile increasing the groundwater recharge.
Keywords: HEC-ResSim model; Holistic flood management; Pond cascade system